Pengaruh Penggunaan Media Poster Digital Terhadap Pemahaman Siswa Kelas V SDN 13 Pangkalanbaru - Ilham Ilham; Fandi Nugroho; Hevitria (JBES (Journal Basic Education Skills), 2025)
This study was driven by students' absence of understanding and limited use of various learning methods. The goal of this study is to look into the effect of digital poster media on the learning of the digestive system in humans within Class V at SD Negeri 13 Pangkalanbaru. This research employed a quantitative approach via a pre-experimental design, which was a single-group pretest-posttest. The sampling technique used was saturation sampling. Data was acquired via testing. The Shapiro-Wilk normality test and paired sample t-test were employed to evaluate hypotheses. The results showed that the value of the first normality test was 0.133 > 0.05, and the follow-up normality test was 0.102 > 0.05, indicating that the data had a usual distribution. Meanwhile, a hypothesis test using a paired sample t-test produced a value of significance of 0.000 0.05. It means that Ho was rejected but Ha was accepted. As a consequence, it can be concluded that using digital poster medium increases students' understanding of the issue in Grade V at SD Negeri 13 Pangkalanbaru.